Method for reducing laser damage in solar cell and application

CN119604063APending Publication Date: 2025-03-11JIETAI NEW ENERGY TECHNOLOGY (SUZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411665161.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-20
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

During the preparation of solar cells, due to the barrier of the oxide layer on the outer surface of the polycrystalline silicon layer, the laser doping efficiency is low and the doping concentration is uneven, which increases production costs and reduces the photoelectric conversion efficiency.

Method used

By depositing the tunneled silicon oxide layer and polysilicon layer on the back of the polysilicon layer, and removing the oxide layer with pickling or plasma gas bombardment, contacting the polysilicon layer directly, and then laser doping with low energy density is performed to optimize the diffusion path of the doping source.

Benefits of technology

The doping concentration and uniformity in the polysilicon layer are improved, the field passivation effect of the battery is enhanced, the contact resistance is reduced, the photoelectric conversion efficiency of the solar cell is improved, and the laser damage and production costs are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119604063A_ABST
    Figure CN119604063A_ABST
Patent Text Reader

Abstract

The invention relates to a method for reducing laser damage in a solar cell, which comprises the following steps of substrate deposition, oxide layer removal, PN doping source preparation, laser doping, cleaning, annealing treatment, texturing, passivation, metallization and the like, and is characterized in that the oxide layer generated on the surface of a polycrystalline silicon layer is removed in a physical or chemical mode; by adopting the laser with low energy density, the uniform diffusion of the doping source in the polycrystalline silicon layer can be realized, laser damage to a silicon wafer is not easily caused, and the method is suitable for large-area doping, so that the effects of reducing the laser damage, improving the doping concentration uniformity and reducing the production cost can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a method for reducing laser damage in solar cells. Background Art

[0002] Solar cells are optoelectronic devices that convert light energy into electrical energy. Due to their clean, renewable, and environmentally friendly advantages, they have become an important direction for global energy development. Among them, TOPCon (tunneling oxide passivation contact technology) and TBC (tunneling oxide passivation back contact) solar cells are characterized by first using a chemical method to prepare an ultra-thin silicon oxide layer SiOx on the back of the silicon wafer, and then depositing a doped polysilicon layer Poly. The two together form a passivation contact structure as the back passivation layer of the battery. The process routes used for its preparation usually include LPCVD (low pressure chemical vapor deposition) and PECVD (plasma enhanced chemical vapor deposition).

[0003] Whether it is the LPCVD or PECVD technical route, an oxide layer will be generated on the outer surface of the generated Poly. When the doping source diffuses into the Poly layer, it will be blocked by the surface oxide layer, resulting in a low doping concentration in the Poly and poor contact performance. In the preparation process of solar cells, laser technology is widely used, such as laser doping process. Unlike high-temperature doping, laser doping is to irradiate the semiconductor material with a laser beam to generate plasma inside it, thereby achieving the purpose of doping. This process can improve the performance of solar cells by precisely controlling the location and concentration of doping.

[0004] At present, during the preparation process of related TOPCon and TBC solar cells, the oxide layer generated on the outer surface of the polysilicon layer will block the laser doping. On the one hand, the blocking of the oxide layer will affect the diffusion of the doping source, resulting in a low doping concentration inside the polysilicon layer. If the laser energy is increased to break through the blocking of the oxide layer and thus ensure the doping concentration, the production cost of the solar cell will increase. The higher laser energy is also likely to increase the damage to the silicon wafer due to the laser thermal effect, which will cause laser damage to the silicon wafer and reduce the photoelectric conversion efficiency of the solar cell. On the other hand, due to the blocking of the oxide layer, the diffusion path of the doping source into the polysilicon layer is extended, resulting in uneven doping concentration and thus reducing the performance of the solar cell. Summary of the invention

[0005] Poly as described in this application refers to polycrystalline silicon;

[0006] SiOx as described in this application refers to silicon oxide;

[0007] BSG mentioned in this application refers to Boron Silicate Glass;

[0008] PSG mentioned in this application refers to Phospho Silicate Glass;

[0009] TOPCon mentioned in this application refers to Tunnel Oxide Passivated Contact (tunneling silicon oxide passivation contact technology);

[0010] The TBC mentioned in this application refers to Tunneling Oxide Passivated Contact Back Contact (Tunneling Oxide Passivated Back Contact);

[0011] ALD as described in this application refers to Atom Layer Deposition;

[0012] The LPCVD described in this application refers to Low Pressure Chemical Vapor Deposition (low pressure chemical vapor deposition);

[0013] PECVD described in this application refers to Plasma Enhanced Chemical Vapor Deposition (plasma enhanced chemical vapor deposition);

[0014] The ICPECVD described in this application refers to Inductively coupled plasma enhanced chemical vapor deposition.

[0015] In order to increase the doping concentration and doping uniformity of laser doping, while reducing laser damage to silicon wafers and improving the photoelectric conversion efficiency of solar cells, the present application provides a method for reducing laser damage in solar cells.

[0016] A method for reducing laser damage in a solar cell comprises the following steps:

[0017] (1) Substrate deposition: A tunneling silicon oxide layer is first deposited on the back of the polished silicon substrate by LPCVD or PECVD, and then a polysilicon layer is deposited;

[0018] (2) Removing the oxide layer: removing the oxide layer on the outer surface of the polysilicon layer by acid pickling or plasma gas bombardment;

[0019] (3) Preparation of PN doping source: Printing nano-paste containing boron and nano-paste containing phosphorus on the outer surface of the polysilicon layer to form a PN region, and drying after printing;

[0020] (4) Laser doping: A low-energy-density laser is used to perform large-area laser doping on the PN region. The laser wavelength is 300-680 nanometers and the laser energy density is 0.4-0.6 J / cm 2 ;

[0021] (5) Cleaning: Cleaning the substrate to remove impurities and residues formed on the surface of the P-type region and the N-type region;

[0022] (6) Annealing: Annealing the cleaned substrate to activate the doped region;

[0023] The annealed substrate is subjected to texturing, passivation and metallization processes in sequence to form a battery structure;

[0024] The pickling operation steps are: immersing the substrate in step (1) in a hydrofluoric acid solution with a concentration of 5wt%-10wt% for 2-10 minutes, then rinsing with deionized water and drying to remove the oxide layer.

[0025] By adopting the above technical solution, the oxide layer is removed so that the doping source of laser doping can directly contact the polysilicon layer without breaking through the barrier of the oxide layer, thereby increasing the doping concentration in the polysilicon layer, thereby enhancing the field passivation effect of the battery, increasing the opening voltage and fill factor, reducing the contact resistance, and thus improving the battery efficiency; on the other hand, the removal of the oxide layer optimizes the diffusion path of the doping source, and a low-energy-density laser can be used to achieve uniform diffusion of the doping source in the polysilicon layer, which is not easy to cause laser damage to the silicon wafer, thereby achieving the purpose of reducing laser damage, improving the uniformity of doping concentration and reducing production costs.

[0026] Optionally, the operating steps of the plasma gas bombardment are: using PECVD or ICPECVD, the substrate is bombarded with plasma gas via NH3, CF4, CHF3 or H2, with a power of 1000-10000W, a bombardment time of 1-10min, and an air intake of 1000-9000sccm, to remove the oxide layer on the outer surface of the Poly layer or after the step of depositing the Poly layer is completed, N2 is purged with an air intake of 1000-9000sccm to isolate O2 from the oxide generated on the Poly surface.

[0027] By adopting the above technical solution and using the plasma gas bombardment method, the polysilicon layer on the back of the substrate will not be damaged, while ensuring the effective removal of the oxide layer on the surface of the polysilicon layer.

[0028] Optionally, in step (4), the wavelength of the green laser is 530-535 nm, and the laser energy density is 0.45-0.55 J / cm 2.

[0029] By adopting the above technical solution, a low energy density (i.e. 0.45-0.55 J / cm 2 ) can effectively reduce laser damage and has the advantage of good doping effect.

[0030] Optionally, the particle size of the nano slurry in step (3) is 40-60 nm.

[0031] By adopting the above technical solution and adding nano-paste as a doping source, the diffusion of the doping source in the Poly layer is made more uniform, thereby improving the uniformity of the doping concentration and further improving the performance of the solar cell.

[0032] Optionally, the thickness of the silicon-based substrate is 0.1-0.5 mm, and the resistivity of the silicon-based substrate is 1-10 ohm·cm.

[0033] Optionally, the thickness of the tunneling silicon oxide layer is 0.5-5 nm, and the thickness of the polysilicon layer is 100-400 nm.

[0034] Optionally, the specific operation of the cleaning step is: first use a hydrochloric acid solution for preliminary cleaning, and then perform ultrasonic cleaning, and the cleaning time is 10-30 minutes.

[0035] By adopting the above technical solution, impurities and residues formed on the surface of the P-type region and the N-type region are removed through a cleaning step, thereby ensuring the performance and quality of the solar cell.

[0036] Optionally, the annealing temperature is 800-1000° C., and the annealing time is 20-100 minutes.

[0037] By adopting the above technical solution, the cleaned substrate is annealed to activate the doped area, improve the electrical performance of the solar cell, and achieve local P + or N + The annealing treatment helps to promote the doping of the Poly layer, tunneling layer and silicon substrate.

[0038] In a second aspect, the present application provides an application of a method for reducing laser damage in solar cells.

[0039] The invention discloses an application of a method for reducing laser damage in a solar cell, which is used for preparing large-area laser doping of a solar cell through a tunneling oxide layer and a polysilicon layer.

[0040] Optional for large area laser doping of TBC cells or TOPCon cells.

[0041] By adopting the above technical solution, the laser doping of the present application is suitable for large-area doping, the width of the doping area is 150 microns or the single area accounts for 16% of the total area, and the spot size is optimally 50-300 microns in side length. The width of the doping area is 250 microns or the single area accounts for 25% of the total area, and the spot size is optimally 100-200 microns in side length.

[0042] In summary, this application has the following beneficial effects:

[0043] 1. The oxide layer is removed by pickling or plasma gas bombardment, so that the doping source of laser doping can directly contact the polysilicon layer without breaking through the barrier of the oxide layer, thereby increasing the doping concentration in the polysilicon layer, thereby enhancing the field passivation effect of the battery, increasing the opening voltage and fill factor, reducing the contact resistance, and thus improving the battery efficiency; on the other hand, the removal of the oxide layer optimizes the diffusion path of the doping source, and a low-energy-density laser can be used to achieve uniform diffusion of the doping source in the polysilicon layer, which is not easy to cause laser damage to the silicon wafer, thereby achieving the purpose of reducing laser damage, improving the uniformity of doping concentration, and reducing production costs.

[0044] 2. The laser doping method of the present application is suitable for large-area doping. The width of the doping area is 150 microns or the single area accounts for 16% of the total area, and the spot size is optimally 50-300 microns in length. The width of the doping area is 250 microns or the single area accounts for 25% of the total area, and the spot size is optimally 100-200 microns in length. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is the product structure of the TBC battery made in Examples 1.1-1.3. DETAILED DESCRIPTION

[0046] The experimental methods in the following examples of the present invention, where no specific conditions are specified, are usually carried out under conventional conditions or under conditions recommended by the manufacturers. The various commonly used chemical reagents used in the examples are all commercially available products.

[0047] Examples 1.1-1.3

[0048] A method for reducing laser damage in a solar cell comprises the following steps:

[0049] (1) Substrate deposition: a tunneling silicon oxide layer is first deposited on the back of the polished silicon substrate by LPCVD, and then a polysilicon layer is deposited; the thickness of the silicon substrate is 0.15 mm, the resistivity is 1 ohm·cm, the thickness of the tunneling silicon oxide layer is 1.5 nm, and the thickness of the polysilicon layer is 300 nm;

[0050] (2) Removing the oxide layer: using pickling to remove the oxide layer on the outer surface of the polysilicon layer;

[0051] The pickling operation steps are as follows: immersing the substrate in step (1) in a hydrofluoric acid solution with a concentration of 5-10 wt% for 2-10 min, then rinsing with deionized water and drying to remove the oxide layer.

[0052] (3) Preparation of PN doping source: Printing nano-paste containing boron and nano-paste containing phosphorus on the outer surface of the polysilicon layer, the particle size of the nano-paste is 50 nm, forming a PN region, and drying after printing;

[0053] (4) Laser doping: A low-energy-density laser is used to perform large-area laser doping on the PN region. The laser wavelength is 532 nanometers and the laser energy density is 0.45-0.55 J / cm 2 ;

[0054] (5) Cleaning: The substrate is cleaned. The specific operation of the cleaning step is: first use a hydrochloric acid solution for preliminary cleaning, and then perform ultrasonic cleaning for 10 minutes to remove impurities and residues formed on the surface of the P-type region and the N-type region;

[0055] (6) Annealing: The cleaned substrate is annealed at a temperature of 800-1000° C. for 20-100 minutes to activate the doped region;

[0056] (7) Texturing: The front side of the substrate is texturized, and then placed in a 5 wt % hydrofluoric acid solution to remove BSG and PSG generated by annealing, and then cleaned to remove surface contaminants;

[0057] (8) Passivation: A first passivation layer is first deposited on the front and back sides of the substrate using an ALD process, and then a first anti-reflection layer and a second anti-reflection layer are sequentially deposited using a PECVD process;

[0058] (9) Metallization: Print the first electrode and the second electrode on the back of the substrate and sinter them to form a complete battery structure. Figure 1 shown.

[0059] The preparation process parameters of Examples 1.1 to 1.3 are shown in Table 1.

[0060] Table 1 Preparation process parameters of Examples 1.1-1.3

[0061]

[0062] Example 2.1

[0063] A method for reducing laser damage in solar cells, which is different from Example 1.2 in that in step (2), the oxide layer is removed by plasma gas bombardment. The operation steps are: using PECVD, the substrate is bombarded with CF4 plasma gas at a power of 1000 W, a bombardment time of 10 min, and an air intake of 1000 sccm to remove the oxide layer on the outer surface of the Poly layer or after the step of depositing the Poly layer is completed, N2 is purged with an air intake of 9000 sccm to isolate O2 from the oxide generated on the Poly surface.

[0064] Example 2.2

[0065] A method for reducing laser damage in solar cells, which is different from Example 1.2 in that in step (2), the oxide layer is removed by plasma gas bombardment. The operating steps are: using ICPECVD, the substrate is bombarded with CHF3 plasma gas at a power of 10000 W, a bombardment time of 1 min, and an air intake of 9000 sccm to remove the oxide layer on the outer surface of the Poly layer or after the Poly layer deposition step is completed, N2 is purged with an air intake of 1000 sccm to isolate O2 from the oxide generated on the Poly surface.

[0066] Example 2.3

[0067] A method for reducing laser damage in solar cells, which is different from Example 1.2 in that in step (2), the oxide layer is removed by plasma gas bombardment. The operating steps are: using ICPECVD, the substrate is bombarded with H2 plasma gas at a power of 5000 W, a bombardment time of 5 min, and an air intake of 4000 sccm to remove the oxide layer on the outer surface of the Poly layer or after the Poly layer deposition step is completed, N2 is purged with an air intake of 5000 sccm to isolate O2 from the oxide generated on the Poly surface.

[0068] Example 2.4

[0069] A method for reducing laser damage in solar cells, which is different from Example 1.2 in that in step (2), the oxide layer is removed by plasma gas bombardment. The operating steps are: using PECVD, the substrate is bombarded with NH3 plasma gas at a power of 7000 W, a bombardment time of 4 min, and an air intake of 6000 sccm to remove the oxide layer on the outer surface of the Poly layer or after the step of depositing the Poly layer is completed, N2 is purged with an air intake of 5000 sccm to isolate O2 from the oxide generated on the Poly surface.

[0070] Comparative Example 1

[0071] A method for reducing laser damage in a solar cell, which is different from Example 1.2 in that step (2) of removing the oxide layer is not performed, and the remaining conditions and parameters are the same as those of Example 1.2.

[0072] Comparative Example 2

[0073] A method for reducing laser damage in solar cells, which is different from Example 1.2 in that the cleaning time of hydrofluoric acid in step (2) is 30 seconds, and the other condition parameters are the same as those in Example 1.2.

[0074] Comparative Example 3

[0075] A method for reducing laser damage in a solar cell, which is different from Example 1.2 in that the laser energy density in step (4) is 0.8 J / cm 2 .

[0076] Performance testing

[0077] 1.J0 test

[0078] The manufactured battery cells were subjected to J0 test using the sinton WCT120 equipment.

[0079] The J0 test is used to characterize the damage of the cell. J0 refers to the degree of recombination in the highly doped area of ​​the silicon wafer. However, if the surface can be effectively passivated, its recombination degree can be reduced, and J0 will also decrease. The passivation differences of the test samples are mainly reflected in the doping concentration of the polysilicon layer and laser damage. The doping concentration of the polysilicon layer affects the field passivation effect and can reduce the recombination of carriers on the surface. Laser damage is mainly reflected in lattice damage, lattice defects, etc. The greater the damage, the higher the carrier recombination rate, and the increase in J0. For each embodiment and comparative example, the J0 of 5 different positions on the back of the substrate after laser doping is randomly tested, and the average value is calculated.

[0080] 2. Square resistance test

[0081] The square resistance was tested using a square resistance tester 4P AUTOMATIC FOUR POINT PRROBE METER. The larger the standard deviation of the square resistance, the worse the doping uniformity. For each embodiment and comparative example, the square resistance at 5 different positions on the back side of the substrate after laser doping was randomly tested, and the standard deviation was calculated.

[0082] 3. Battery performance test

[0083] The manufactured solar cells are tested using a PL+IV all-in-one automatic sorting machine for solar cells.

[0084] Since there is no substantial statistical difference between the test results of Examples 1.1-1.3 and Examples 2.1-2.4 of the present application, only the test results of Example 1.2 are used as an example to compare with the test data of the comparative example.

[0085] The J0 test results of Example 1.2 and Comparative Examples 1-3 are shown in Table 2, the square resistance test results of Example 1.2 and Comparative Examples 1-3 are shown in Table 3, and the battery performance test of Example 1.2 and Comparative Examples 1-3 is shown in Table 4.

[0086] Table 2 J0 test results of Example 1.2 and Comparative Examples 1-3

[0087] Group <![CDATA[J01]]> <![CDATA[J02]]> <![CDATA[J03]]> <![CDATA[J04]]> <![CDATA[J05]]> average value Example 1.2 12.29 12.35 12.13 12.33 12.18 12.26 Comparative Example 1 26.12 26.15 26.02 26.19 26.22 26.14 Comparative Example 2 20.12 20.26 20.15 20.09 20.21 20.17 Comparative Example 3 87.35 87.62 88.12 87.98 88.22 87.86

[0088] Table 3 Square resistance test results of Example 1.2 and Comparative Examples 1-3

[0089]

[0090]

[0091] Table 4 Battery performance test results of Example 1.2 and Comparative Examples 1-3

[0092]

[0093] Combining the test results of Example 1.2 of the present application and Comparative Example 1, it can be seen that the test results of Example 1.2 are better than those of Comparative Example 1. The reason may be that when the oxide layer is not removed, under the laser energy of Example 1.2, the doping concentration does not meet the requirements, and at the same time, the doping uniformity is reduced due to the presence of the oxide layer, and the battery performance is reduced.

[0094] Combining the test results of Example 1.2 of the present application and Comparative Example 2, it can be seen that the test results of Example 1.2 are better than those of Comparative Example 2. This is because when the hydrofluoric acid cleaning time is only 30s, the cleaning time is insufficient, and the oxide layer on the outer surface of the poly is not cleaned cleanly, resulting in the doping concentration not meeting the requirements. At the same time, the doping uniformity is reduced due to the presence of the oxide layer, and the battery performance is reduced.

[0095] Combining the test results of Example 1.2 and Comparative Example 3, it can be seen that the test result of Example 1.2 is better than that of Comparative Example 3. The J0 of Comparative Example 3 is higher than that of Example 1.2. This is mainly because when the laser energy density increases to 0.8 J / cm 2 At this time, the lattice defects caused by the laser increase, which increases the recombination rate in the silicon wafer, shortens the minority carrier lifetime, increases laser damage, and reduces battery performance.

[0096] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for reducing laser damage in a solar cell, characterized in that: The following steps are involved: (1) Substrate deposition: A tunneling silicon oxide layer is first deposited on the back of the polished silicon substrate by LPCVD or PECVD, and then a polysilicon layer is deposited; (2) Removing the oxide layer: removing the oxide layer on the outer surface of the polysilicon layer by acid pickling or plasma gas bombardment; (3) Preparation of PN doping source: Printing nano-paste containing boron and nano-paste containing phosphorus on the outer surface of the polysilicon layer to form a PN region, and drying after printing; (4) Laser doping: A low-energy-density laser is used to perform large-area laser doping on the PN region. The laser wavelength is 300-680 nanometers and the laser energy density is 0.4-0.6 J / cm 2 ; (5) Cleaning: Cleaning the substrate to remove impurities and residues formed on the surface of the P-type region and the N-type region; (6) Annealing: Annealing the cleaned substrate to activate the doped region; The annealed substrate is subjected to texturing, passivation and metallization processes in sequence to form a battery structure; The pickling operation steps are: immersing the substrate in step (1) in a hydrofluoric acid solution with a concentration of 5wt%-10wt% for 2-10 minutes, then rinsing with deionized water and drying to remove the oxide layer.

2. A method for reducing laser damage in solar cells according to claim 1, characterized in that: The operation steps of the plasma gas bombardment are: using PECVD or ICPECVD, the substrate is bombarded with plasma gas by NH3, CF4, CHF3 or H2, the power is 1000-10000W, the bombardment time is 1-10min, the air intake is 1000-9000sccm, the oxide layer on the outer surface of the Poly layer is removed or after the step of depositing the Poly layer is completed, N2 is purged, and the air intake is 1000-9000sccm to isolate O2 from the oxide generated on the Poly surface.

3. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The wavelength of the green laser in step (4) is 530-535 nm, and the laser energy density is 0.45-0.55 J / cm 2 .

4. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The particle size of the nano slurry in step (3) is 40-60 nm.

5. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The thickness of the silicon-based substrate is 0.1-0.5 mm, and the resistivity of the silicon-based substrate is 1-10 ohm·cm.

6. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The thickness of the tunneling silicon oxide layer is 0.5-5 nm, and the thickness of the polysilicon layer is 100-400 nm.

7. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The specific operation of the cleaning step is: first use hydrochloric acid solution for preliminary cleaning, and then perform ultrasonic cleaning, and the cleaning time is 10-30 minutes.

8. The method for reducing laser damage in solar cells according to claim 1, characterized in that: The annealing temperature is 800-1000° C., and the annealing time is 20-100 minutes.

9. An application of the method for reducing laser damage in solar cells according to any one of claims 1 to 8, for preparing large-area laser doping of solar cells through tunnel oxide layers and polysilicon layers.

Citation Information

Cited By

  • Preparation method of solar cell and solar cell

    CN120152435A

  • Photovoltaic cell preparation method, photovoltaic cell, laminated cell and photovoltaic cell assembly

    CN120358831A